Intake and metabolism of omega-3 and omega-6 polyunsaturated fatty acids: nutritional implications for cardiometabolic diseases - Schulze, Matthias B; Minihane, Anne Marie; Saleh, Rasha Noureldin M; Risérus, Ulf (The lancet. Diabetes & endocrinology, 2020)
Prospective observational studies support the use of long-chain omega-3 polyunsaturated fatty acids (PUFAs) in the primary prevention of atherosclerotic cardiovascular disease; however, randomised controlled trials, have often reported neutral findings. There is a long history of debate about the potential harmful effects of a high intake of omega-6 PUFAs, although this idea is not supported by prospective observational studies or randomised controlled trials. Health effects of PUFAs might be influenced by Δ-5 and Δ-6 desaturases, the key enzymes in the metabolism of PUFAs. The activity of these enzymes and modulation by variants in encoding genes (FADS1-2-3 gene cluster) are linked to several cardiometabolic traits. This Review will further consider non-genetic determinants of desaturase activity, which have the potential to modify the availability of PUFAs to tissues. Finally, we discuss the consequences of altered desaturase activity in the context of PUFA intake, that is, gene-diet interactions and their clinical and public health implications.Prospective observational studies support the use of long-chain omega-3 polyunsaturated fatty acids (PUFAs) in the primary prevention of atherosclerotic cardiovascular disease; however, randomised controlled trials, have often reported neutral findings. There is a long history of debate about the potential harmful effects of a high intake of omega-6 PUFAs, although this idea is not supported by prospective observational studies or randomised controlled trials. Health effects of PUFAs might be influenced by Δ-5 and Δ-6 desaturases, the key enzymes in the metabolism of PUFAs. The activity of these enzymes and modulation by variants in encoding genes (FADS1-2-3 gene cluster) are linked to several cardiometabolic traits. This Review will further consider non-genetic determinants of desaturase activity, which have the potential to modify the availability of PUFAs to tissues. Finally, we discuss the consequences of altered desaturase activity in the context of PUFA intake, that is, gene-diet interactions and their clinical and public health implications.